Reaksi Pasar Saham Terhadap Pengumuman Kebijakan Larangan Ekspor CPO dan Turunannya - Kusuma, Farisha Ardra; Noor, Trisna Insan (Universitas Galuh, 2024)
This study aimed to analyze the reaction of the stock market of palm oil companies listed on the Indonesia Stock Exchange to the announcement of a ban on the export of CPO and its derivatives regulated in the Regulation of the Minister of Trade of the Republic of Indonesia Number 22 of 2022 regarding Temporary Prohibition on the Export of Crude Palm Oil, Refined, Bleached And Deodorized Palm Oil, Refined, Bleached And Deodorized Palm Olein, and Used Cooking Oil, which were announced on the 27th of April 2022. This study examined 17 shares of palm oil companies using the event study research method with indicators of abnormal return. In this study, the used estimation period is 30 days and the event window is 11 days. Two data analysis techniques used are descriptive statistical analysis and inferential statistical analysis using the non-parametric Wilcoxon Signed Ranks Test. The test results showed that there were differences in average abnormal return before and after the announcement of the CPO and its derivatives export ban policy.